2006
DOI: 10.1063/1.2405387
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial self-cleaning in atomic layer deposition of HfO2 gate dielectric on In0.15Ga0.85As

Abstract: An interfacial self-cleaning phenomenon was found in the atomic layer deposition of HfO2 on In0.15Ga0.85As∕GaAs substrate using Hf(NCH3C2H5)4, i.e., TEMAH, and H2O as the precursors. The native oxides of InGaAs were all satisfactorily removed from the interface through ligand exchange (substitution) reactions with the TEMAH precursor. It relieves the Fermi-level pinning in the HfO2∕InGaAs heterostructure, as verified by the clear transition from accumulation to depletion in high-frequency capacitance-voltage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
104
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 16 publications
2
104
0
Order By: Relevance
“…Exposure to the TMA precursor with H 2 O at 300°C results in the reduction of the As 3+ oxidation state intensity to below XPS detectable limits, consistent with previous reports. 2,3,6 In contrast, after 1 nm HfO 2 deposition, the As 5+ oxidation state intensity has been reduced, while a remnant As 3+ state intensity remains. Recent studies by our group have shown that it is in fact the metal-organic precursor half-cycle ͑and not the subsequent oxidation with H 2 O͒ which removes the native oxides and most of the reduction occurs during the first TMA pulse.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Exposure to the TMA precursor with H 2 O at 300°C results in the reduction of the As 3+ oxidation state intensity to below XPS detectable limits, consistent with previous reports. 2,3,6 In contrast, after 1 nm HfO 2 deposition, the As 5+ oxidation state intensity has been reduced, while a remnant As 3+ state intensity remains. Recent studies by our group have shown that it is in fact the metal-organic precursor half-cycle ͑and not the subsequent oxidation with H 2 O͒ which removes the native oxides and most of the reduction occurs during the first TMA pulse.…”
mentioning
confidence: 91%
“…Dalapati et al reported that some remnant oxides are detected after similar ALD processes at 300°C. 4 Huang et al 5 and Chang et al 6 have reported the removal of As oxides on InGaAs using Al 2 O 3 ͑TMA͒ and HfO 2 ͓tetrakis ͑ethylmethylamino͒ hafnium ͑TEMA-Hf͔͒, respectively. Shahrjerdi et al 7 reported no self-cleaning using tetrakis ͑dimethyl-amino͒ hafnium on GaAs.…”
mentioning
confidence: 99%
“…Control of the III-V/high-k interface is a critical issue for the realization and stable operation of high-electron-mobility metal-insulator-semiconductor field-effect transistors (MISFETs). [1][2][3][4][5][6][7][8][9][10][11] Recent progress in the atomic layer deposition (ALD) technique has allowed for the formation of high-k films on III-V materials with an abrupt and high quality interface. However, a high density of interface states (D it ) still exists, which causes problems such as Fermi level pinning, large hysteresis, instability, mobility deterioration, and an increase in threshold voltage.…”
mentioning
confidence: 99%
“…Due to favorable Gibbs free energies, Al 2 O 3 formation is energetically preferred to native oxide of InAs and GaSb. Alternatively, As atoms that form As 2 O 3 or In atoms in an In 2 O 3 molecule are replaced by Al +3 atoms in the TMA molecule [22]. Similar reaction pathways with oxides of other metal atoms are also possible.…”
Section: Resultsmentioning
confidence: 99%